Semaphorin 3E‐Plexin‐D1 Pathway Downstream of the Luteinizing Hormone Surge Regulates Ovulation, Granulosa Cell Luteinization, and Ovarian Angiogenesis in Mice - Hanxue Zhang; Jimmy Dhillon; Paul D. Soloway; Bo Shui; Seoyeon Lee; Jennifer K. Grenier; Paul R. Munn; M. Cecilia Ljungberg; Rebecca B Williams; Rainer B. Lanz; Yu‐Hsiang Liao; Yi A. Ren (Advanced Science)
Abstract Ovulation is induced by the luteinizing hormone (LH) surge and accompanied by granulosa cell luteinization and ovarian angiogenesis. Semaphorin 3E (Sema3E)‐Plexin‐D1 pathway regulates angiogenesis in other tissues, but its role in the ovary is unknown. Evidence indicates that Sema3E‐Plexin‐D1 pathway plays an important role in the mouse ovary. The expression of Sema3E and its receptor, Plexin‐D1, is dynamically regulated in the mouse ovary downstream of the LH surge. This regulation requires the modulation of chromatin accessibility by CCAAT/enhancer‐binding proteins α and β. Intraovarian injection of recombinant Sema3E results in reduced ovulation, impaired corpus luteum formation, and aberrant ovarian angiogenesis. These in vivo physiological abnormalities are consistent with altered expression of genes regulating these processes, and with data from in vitro cultured granulosa cells and ovarian stromal tissues treated with Sema3E or neutralizing antibody of Plexin‐D1. The findings pinpoint Sema3E‐Plexin‐D1 pathway as a potential therapeutic target for fertility and infertility management.